Geranylgeranyl pyrophosphate depletion by statins compromises skeletal muscle insulin sensitivity. Issue 6 (12th August 2022) - Wang, Lai; Zheng, Zuguo; Zhu, Lijun; Meng, Lingchang; Liu, Hanling; Wang, Keke; Chen, Jun; Li, Ping; Yang, Hua
Abstract: Background: Statins are widely prescribed cholesterol‐lowering drugs but have been shown to increase the risk of type 2 diabetes mellitus. However, the molecular mechanisms underlying the diabetogenic effect of statins are still not fully understood. Methods: The effects of geranylgeranyl transferase I and II (GGTase I and II) inhibition on insulin‐stimulated glucose uptake and GLUT4 translocation, and the dependence of these effects on insulin signalling were investigated in skeletal muscle cells. The protective effects of geranylgeranyl pyrophosphate (GGPP) and its precursor geranylgeraniol (GGOH) on simvastatin‐induced insulin resistance were evaluated in vitro and in vivo . The effect of GGTase II inhibition in skeletal muscle on insulin sensitivity in vivo was confirmed by adeno‐associated virus serotype 9 (AAV9)‐mediated knockdown of the specific subunit of GGTase II, RABGGTA. The regulatory mechanisms of GGTase I on insulin signalling and GGTase II on insulin‐stimulated GLUT4 translocation were investigated by knockdown of RhoA, TAZ, IRS1, geranylgeranylation site mutation of RhoA, RAB8A, and RAB13. Results: Both inhibition of GGTase I and II mimicked simvastatin‐induced insulin resistance in skeletal muscle cells. GGPP and GGOH were able to prevent simvastatin‐induced skeletal muscle insulin resistance in vitro and in vivo . GGTase I inhibition suppressed the phosphorylation of AKT (Ser473) (−51.3%, P  < 0.01), while GGTase II inhibition had no effect on it. AAV9‐mediated knockdown of RABGGTA in skeletal muscle impaired glucose disposal without disrupting insulin signalling in vivo (−46.2% for gastrocnemius glucose uptake, P  < 0.001; −52.5% for tibialis anterior glucose uptake, P  < 0.001; −17.8% for soleus glucose uptake, P  < 0.05; −31.4% for extensor digitorum longus glucose uptake, P  < 0.01). Inhibition of RhoA, TAZ, IRS1, or geranylgeranylation deficiency of RhoA attenuated the beneficial effect of GGPP on insulin signalling in skeletal muscle cells. Geranylgeranylation deficiency of RAB8A inhibited insulin‐stimulated GLUT4 translocation and concomitant glucose uptake in skeletal muscle cells (−42.8% for GLUT4 translocation, P  < 0.01; −50.6% for glucose uptake, P  < 0.001). Conclusions: Geranylgeranyl pyrophosphate regulates glucose uptake via GGTase I‐mediated insulin signalling‐dependent way and GGTase II‐mediated insulin signalling‐independent way in skeletal muscle. Supplementation of GGPP/GGOH could be a potential therapeutic strategy for statin‐induced insulin resistance.